Effects of temperature on the interaction between amphibian skin bacteria and Batrachochytrium dendrobatidis - Matthew J. Robak; Veronica Saenz; Veronica Saenz; Esmee de Cortie; Corinne L. Richards-Zawacki (Frontiers in Microbiology, 2023)
Symbiotic relationships between animals and microbes are important for a range of functions, from digestion to protection from pathogens. However, the impact of temperature variation on these animal-microbe interactions remains poorly understood. Amphibians have experienced population declines and even extinctions on a global scale due to chytridiomycosis, a disease caused by chytrid fungi in the genus Batrachochytrium. Variation in susceptibility to this disease exists within and among host species. While the mechanisms generating differences in host susceptibility remain elusive, differences in immune system components, as well as variation in host and environmental temperatures, have been associated with this variation. The symbiotic cutaneous bacteria of amphibians are another potential cause for variation in susceptibility to chytridiomycosis, with some bacterial species producing antifungal metabolites that prevent the growth of Bd. The growth of both Bd and bacteria are affected by temperature, and thus we hypothesized that amphibian skin bacteria may be more effective at preventing Bd growth at certain temperatures. To test this, we collected bacteria from the skins of frogs, harvested the metabolites they produced when grown at three different temperatures, and then grew Bd in the presence of those metabolites under those same three temperatures in a three-by-three fully crossed design. We found that both the temperature at which cutaneous bacteria were grown (and metabolites produced) as well as the temperature at which Bd is grown can impact the ability of cutaneous bacteria to inhibit the growth of Bd. While some bacterial isolates showed the ability to inhibit Bd growth across multiple temperature treatments, no isolate was found to be inhibitive across all combinations of bacterial incubation or Bd challenge temperatures, suggesting that temperature affects both the metabolites produced and the effectiveness of those metabolites against the Bd pathogen. These findings move us closer to a mechanistic understanding of why chytridiomycosis outbreaks and related amphibian declines are often limited to certain climates and seasons.